Supplier Capacity and Intermediary Profits: Can Less Be More?. Issue 4 (4th September 2015) - Adida, Elodie; Bakshi, Nitin; DeMiguel, Victor
Abstract : We identify market conditions under which intermediaries can thrive in retailer‐driven supply chains. Our main finding is that, as a consequence of the retailers' leadership position, intermediaries prefer products for which the supply base (existing production capacity) is neither too narrow nor too broad; that is, less existing capacity can result in more intermediary profit. We also show that our main finding is robust to (i) the presence of horizontal competition among retailers and intermediaries, (ii) the existence of exclusive suppliers, and (iii) the ability of the retailers to source directly from the suppliers. Nevertheless, we find that horizontal competition between intermediaries encourages them to carry products with relatively smaller production capacity, whereas exclusive suppliers and direct sourcing encourage intermediaries to carry products with relatively larger installed capacity.